National Trends in the Use of Cardiac Resynchronization Therapy With or Without Implantable Cardioverter-Defibrillator. Issue 3 (19th January 2016) - Lindvall, Charlotta; Chatterjee, Neal A.; Chang, Yuchiao; Chernack, Betty; Jackson, Vicki A.; Singh, Jagmeet P.; Metlay, Joshua P.
Abstract : Background—: Candidates for cardiac resynchronization therapy (CRT) receive either a biventricular pacemaker or a biventricular pacemaker with an implantable cardioverter-defibrillator (CRT-D). Optimal device selection remains challenging because the benefit of implantable cardioverter-defibrillator therapy may not be uniform, particularly in patients at competing risk of nonsudden death. Methods and Results—: In this serial cross-sectional study using the National Inpatient Sample database, we identified 311 086 admissions associated with CRT implant between 2006 to 2012. CRT-D was the most common device type (86.1%), including in patients ≥75 years of age with ≥5 Elixhauser comorbidities (75.5%). Multivariate predictors of CRT-D implant included demographic, clinical, and geographic factors: prior ventricular arrhythmia (rate ratio [RR], 1.14; 95% CI, 1.13–1.14), ischemic heart disease (RR, 1.11; 95% CI, 1.10–1.11), male sex (RR, 1.10; 95% CI, 1.09–1.10), black race (RR, 1.06; 95% CI: 1.04–1.07), and Northeast geographic region (RR, 1.06; 95% CI, 1.04–1.09). There was significant interhospital variation in the use of CRT-D (10–90 percentile range, 72.9%–98.0% CRT-D). Conclusions—: The majority of patients in this contemporary US cohort underwent implantation of CRT-D. Predictors of CRT-D implant included demographic, clinical, and geographic factors. In patient subgroups predicted to have an attenuated benefit from implantable cardioverter-defibrillator therapy (older adults with multiple comorbidities), CRT-D remained the dominant device type. An improved understanding of the determinants of device selection may aid in decision making and ultimately better align patient risk with device benefit at the time of CRT implantation. Abstract : Supplemental Digital Content is available in the text.